HUBUNGAN KADAR GULA DARAH DENGAN TEKANAN DARAH PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS SOKARAJA 1 - Habib Fatah Roniawan; Peppy Octaviani DM; Rani Prabandari (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Type 2 Diabetes Mellitus is a condition when blood glucose in the body is not controlled due to impaired sensitivity of pancreatic cells to produce the hormone insulin. The World Health Organization (WHO) states that there are 422 million people in the world who suffer from diabetes mellitus, an increase of about 8.5% in the adult population and an estimated 2.2 million deaths. The purpose of this study was to determine the characteristics of patients with type 2 diabetes at the Sokaraja 1 Health Center and to find out how the relationship between blood sugar levels and blood pressure of type 2 diabetes mellitus patients at the Sokaraja 1 Health Center. The method used is observational analysis in perspective with a cross sectional approach. The results of this study using the Pearson correlation test showed that 46 patients were majority aged 51 to 60 (39.1%), male 13 patients (28.3%) female 33 patients (711.7%), long time to diagnose diabetes mellitus greater than 1-4 years (73.9%) and there is a relationship between blood sugar levels and blood pressure with a significance value of 0.375.